Desenvolvimento de uma nova liga quaternária Ti25Ta25Nb3Sn para aplicações odontológicas - Seixas, Maurício Rangel [UNESP] (2015)
Metallic biomaterials have been used for biomedical applications, such as cardiovascular, orthopaedics and orthodontics, due to properties. However, although their corrosion resistance these materials can be corrode when exposed oral environment. Metals ion release can produce undesirable toxicity, principally in alloys containing Ni, as NiTi. In this study, a new quaternary alloys with non-cytotoxic elements Ti, Ta, Nb and Sn was processed and evaluated. Alloys were processing in arc melting furnace with argon atmosphere from sheets of commercially pure elements. Ingots will be melted and re-melted ten times at least and homogenized (1000°C for 86.4 ks) for eliminated segregation chemical after cold-worked by swaging. Phases were evaluated by XRD (X-ray diffraction) analysis. Microhardness and tension test was carried out to evaluate mechanical properties. Corrosion behaviors was investigated in fluoride solution by electrochemical polarization. Young's modulus and cytotoxicity of the new alloy were also evaluated. In our study, for quaternary alloy Ti25Ta25Nb3Sn the stabilization of beta phase was maintained. It was observed that the elastic modulus of Ti25Ta25Nb3Sn (65GPa) was lower than CP Ti (105 GPa) and Ti6Al4V (110 GPa) and slightly higher than Ti25Ta25Nb (55GPa) alloy. The addition of Sn suppressed the double yielding verified on ternary alloy Ti25Ta25Nb.Electrochemical studies showed that stable passive oxide film was formed on the Ti25Ta25Nb3Sn surface and non-toxicity was observed after MTT assays. Results obtained showed that Ti25Ta25Nb3Sn alloy is indicated for biomedical applications